2016
DOI: 10.1016/j.bbrc.2016.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin induces insulin resistance in L6 skeletal muscle myotubes by suppressing insulin signaling, GLUT4 expression and GSK-3β phosphorylation

Abstract: Simvastatin is a 3-hydroxy-3-methylglutaryl-CoA reductase inhibitor widely used for the treatment of hypercholesterolemia. Recent data indicates that simvastatin increases the risk of new-onset diabetes by impairing both insulin secretion and insulin sensitivity. However, systematic evaluation of mechanistic pathways is lacking. We aimed to explore the effects of simvastatin on glucose uptake and underlying mechanisms using L6 skeletal muscle myotubes. We performed our experiments at basal and insulin-stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 28 publications
1
20
0
1
Order By: Relevance
“…In vitro studies have shown that treatment of rat skeletal muscle myotubes with simvastatin can reduce the expression of GLUT4. 25 Here, we report similar protein levels of both GLUT4 and HKII in all three groups suggesting no connection between statin-induced myalgia and the expression of these proteins.…”
Section: Discussionsupporting
confidence: 47%
“…In vitro studies have shown that treatment of rat skeletal muscle myotubes with simvastatin can reduce the expression of GLUT4. 25 Here, we report similar protein levels of both GLUT4 and HKII in all three groups suggesting no connection between statin-induced myalgia and the expression of these proteins.…”
Section: Discussionsupporting
confidence: 47%
“…In support of a role for a statin-induced insulin resistance in skeletal muscle, a decreased GLUT-4 expression has been found in L6 myotubes after simvastatin treatment [107]. Alternatively, it has been more recently shown that atorvastatin diminishes GLUT-4 translocation to the plasma membrane without affecting total GLUT-4 protein expression in C2C12 myotubes [108].…”
Section: Skeletal Musclementioning
confidence: 99%
“…The prominent example is simvastatin, which is commonly used in the prevention and treatment of cardiovascular diseases. Simvastatin reduces the phosphorylation of insulin-induced IR at Tyr, IRS-1 at Tyr, and AKT at Thr [22,23]. Therefore, therapy with simvastatin or other statins might be a risk factor for the development of insulin resistance or diabetes.…”
Section: Irs Protein Nodementioning
confidence: 99%